Giftedness from the perspective of research on genius: Some precautionary implications. (September 2022) - Simonton, Dean Keith
The terms giftedness and genius entered the research literature in the 19th century. Although not synonymous, both terms were defined according to potential or actual achievement in a specific domain. However, in the early 20th century, both terms became defined according to performance on domain-generic IQ tests. Given the empirical relations between achievement and intelligence, this transfer of meaning is unjustified. Both giftedness and genius must be defined with respect to potential or actual domain-specific achievements.